SURVIVAL ANALYSIS GANGGUAN PERNAPASAN DENGAN TINGKAT PAJANAN PENCEMARAN UDARA DI DKI JAKARTA (STUDI COHORT PADA MURID SEKOLAH DASAR) - Defriman Djafri (Faculty of Public Health, Andalas University, 2007)
Level of health risk generated by air pollution material to public especially at school children and existence of impact to respiratory symptom. Purpose of this research was wished to know the relationship of respiratory symptom at elementary school with level of air pollution exposure in DKI Jakarta. Prospective cohort was conducted during 3 month of be noted the happening of respiratory illness at the time period. Data is analyzed to apply statistical methods Survival Analysis in STATA 9.2 (license). Result of research it is got that existence of the relationship of respiratory symptom with level of air pollution exposure, From 4 respiratory symptom taken analyzed and in this research, incidence rate at each symptom is got by higher case at region high exposure compared to region low exposure. Conclusion is got approximant 50% base school children experiences case of respiratory symptom based on result of case probability everyone of respiratory symptom observation.